Placental Alkaline Phosphatase Promotes Zika Virus Replication by Stabilizing Viral Proteins through BIP - Jian Chen (American Society for Microbiology, 2020)
ABSTRACT Zika virus (ZIKV) infection during pregnancy causes intrauterine growth defects and microcephaly, but knowledge of the mechanism through which ZIKV infects and replicates in the placenta remains elusive. Here, we found that ALPP, an alkaline phosphatase expressed primarily in placental tissue, promoted ZIKV infection in both human placental trophoblasts and astrocytoma cells. ALPP bound to ZIKV structural and nonstructural proteins and thereby prevented their proteasome-mediated degradation and enhanced viral RNA replication and virion biogenesis. In addition, the function of ALPP in ZIKV infection depends on its phosphatase activity. Furthermore, we demonstrated that ALPP was stabilized through interactions with BIP, which is the endoplasmic reticulum (ER)-resident heat shock protein 70 chaperone. The chaperone activity of BIP promoted ZIKV infection and mediated the interaction between ALPP and ZIKV proteins. Collectively, our findings reveal a previously unrecognized mechanism through which ALPP facilitates ZIKV replication by coordinating with the BIP protein. IMPORTANCE ZIKV is a recently emerged mosquito-borne flavivirus that can cause devastating congenital Zika syndrome in pregnant women and Guillain-Barré syndrome in adults, but how ZIKV specifically targets the placenta is not well understood. Here, we identified an alkaline phosphatase (ALPP) that is expressed primarily in placental tissue and promotes ZIKV infection by colocalizing with ZIKV proteins and preventing their proteasome-mediated degradation. The phosphatase activity of ALPP could be required for optimal ZIKV infection, and ALPP is stabilized by BIP via its chaperone activity. This report provides novel insights into host factors required for ZIKV infection, which potentially has implications for ZIKV infection of the placenta.